2023
DOI: 10.1111/iwj.14299
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetic retinopathy and diabetic foot ulcer in patients with diabetes: A meta‐analysis

Abstract: This study aimed to explore the relationship between diabetic retinopathy (DR) and diabetic foot ulcers (DFUs) to provide evidence for the prevention of diabetic complications. PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Chinese Biomedical Literature Database and Wanfang Data databases were searched from their inception until March 2023 for studies on the relationship between DR and DFU. Two researchers independently screened the literature and extracted data acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a recent meta-analysis of 25 RCTs published up to July 2023, Li et al reported that the use of CHM combined with negative pressure wound therapy for DFU increased the overall effectiveness and ulcer healing rate, as well as reduced the ulcer healing time and post-treatment ulcer area. 36 In another metaanalysis of 26 RCTs published in Chinese (n = 24) and English (n = 2) between 2011 and 2017, Wang et al indicated that conventional therapies plus the use of CHM (i. e. orally, topically or combined) may increase the CUH rate of patients with DFU about twice compared with the conventional therapies alone. Also, their systematic F I G U R E 5 Summary of the authors' judgments about the risk of bias domains within the 28 included randomized controlled trials on the effect of topical and oral administrations of herbal products on the healing of diabetic foot ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis of 25 RCTs published up to July 2023, Li et al reported that the use of CHM combined with negative pressure wound therapy for DFU increased the overall effectiveness and ulcer healing rate, as well as reduced the ulcer healing time and post-treatment ulcer area. 36 In another metaanalysis of 26 RCTs published in Chinese (n = 24) and English (n = 2) between 2011 and 2017, Wang et al indicated that conventional therapies plus the use of CHM (i. e. orally, topically or combined) may increase the CUH rate of patients with DFU about twice compared with the conventional therapies alone. Also, their systematic F I G U R E 5 Summary of the authors' judgments about the risk of bias domains within the 28 included randomized controlled trials on the effect of topical and oral administrations of herbal products on the healing of diabetic foot ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] On the contrary, reviews that performed a meta-analysis or comprehensive synthesis included only studies conducted in China or evaluated Chinese Herbal Medicines (CHM), which may limit the generalizability and applicability of their findings. [31][32][33][34][35][36][37] Yet, recent randomized controlled trials (RCTs) performed in different regions have reported inconsistent findings regarding the potential efficacy of herbal medications in healing DFU. Some studies noted no significant difference in ulcer parameters between treatment and routine care groups, [38][39][40][41][42][43][44][45][46] while others reported the promising effects of herbal preparations on treating DFU.…”
Section: Introductionmentioning
confidence: 99%